Heterogeneous Hydrogenation of Quinoline Derivatives Effected by a Granular Cobalt Catalyst - Timelthaler, Daniel; Topf, Christoph (Synthesis, 2021)
We communicate a convenient method for the pressure hydrogenation of quinolines in aqueous solution by using a particulate cobalt-based catalyst that is prepared in situ from simple Co(OAc)2·4H2O through reduction with abundant zinc powder. This catalytic protocol permits a brisk and atom-efficient access to a variety of 1,2,3,4-tetrahydroquinolines thereby relying solely on easy-to-handle reagents that are all readily obtained from commercial sources. Both the reaction setup assembly and the autoclave charging procedure are conducted on the bench outside an inert-gas-operated containment system, thus rendering the overall synthesis time-saving and operationally very simple.
Keywords: heterogeneous catalysis; hydrogenation; cobalt; zinc; tetrahydroquinolines